Respostas
respondido por:
7
g(x)=3x²-5x+1
a) g(3) = 3 . 3² - 5 . 3 + 1 = 9 - 15 + 1 = -5
b) (-1/3) = 3. (1/3)² - 5. (1/3) + 1 = 3.1/9 - 5/3 + 1 = 1/3 - 5/3 + 1 = -1/3
c) g(0) = 3.0² - 5 . 0 + 1 = 1
a) g(3) = 3 . 3² - 5 . 3 + 1 = 9 - 15 + 1 = -5
b) (-1/3) = 3. (1/3)² - 5. (1/3) + 1 = 3.1/9 - 5/3 + 1 = 1/3 - 5/3 + 1 = -1/3
c) g(0) = 3.0² - 5 . 0 + 1 = 1
respondido por:
0
Resposta: a) g(3) = 3.3²-5.3+1
3.9-15+1
27-15+1
12+1
13
Resposta: b) {a b eu não sei responder}
Resposta: c) g(0) = 3.0²-5.0+1
3.0-0+1
0-0+1
0+1
1
Eu não sei se está certo, mas na minha eu fiz assim.
Perguntas similares
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás